A comparative study of testing semantic web services - Anari, N.; Saboohi, H.; Ahakian, G. (2014)
Web Services provide efficient reusability mechanism, thereby reducing the development time and cost. Mostly the source code of web services is unavailable to other developers who use these services. The manual effort spent by them in testing these web services is very large in order to increase the interoperability. Thus, automated testing needs to be developed for testing these Web services. This paper reviews test cases for Web Services using reduction techniques Pair-Wise Testing (PWT) and Orthogonal Array Testing (OAT) and compares the two techniques with general method. The structure of Web Services is specified using UML diagrams. The pre and post conditions for the service rule are specified using Object Constraint Language (OCL). The framework transforms into WSDLS specifications. These specifications are parsed and transformed into structured DOM tree. Test data set generated by this framework would satisfy the constraints of the WSDL. The test cases are then developed based on the data generated, documented in XML based test files. The number of test cases required by general testing, PWT, OAT are compared and the better testing technique for testing Web Services is determined.